Potensi Asap Cair dari Sekam untuk Meningkatkan Pertumbuhan dan Produksi Padi ( Oryza sativa L.) - Istiqomah Istiqomah; Dian Eka Kusumawati (Universitas Tribhuwana Tunggadewi, 2019)
Rice is the main staple food in Indonesia. The high needs of national rice must be balanced with the high production of rice crops. One of the efforts to increase the production of rice is the application of liquid smoke originated from agricultural waste, namely husk. The research was aimed to determine the effect of the application of husk liquid smoke on rice growth and production. The research used a single-factor randomized block design (RBD) with 5 treatments and 5 replications. The treatments consisted of several concentrations of liquid smoke : 0% (control), 0.5%, 1%, 2%, and 3%. This research employed several stages; land processing, seedling nursery, rice planting, applicating the liquid smoke, fertilizing, maintaining plants, and harvesting. The results showed that the application of husk liquid smoke significantly affected all observational parameters. On the parameters of rice growth and production, the application of 2% liquid smoke showed the best result. The plant height increased by 25.80% and the number of tillers increased by 49.70% compared to the control. The highest increase is in the number of grains per panicle and the weight of 1000 grains was 4,984% and 26.78% respectively.